2020
DOI: 10.1177/0974929220969272
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ethiopian Agricultural Exports: A Dynamic Panel Data Analysis

Abstract: Although the share of developing countries in international trade has been growing over the last two decades, the share of Africa and Ethiopia in international trade has remained below 3 and 0.3 per cent, respectively. More importantly, despite the colossal effort that has been made by the Ethiopian government to remedy the problem of the export sector over the last two decades, the country has faced a twin deficit: trade deficit and fiscal deficit. As a result, the trade balance of Ethiopia has been worsening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…According to Brahmana et al (2018), foreign assets to total global assets are closely associated with the internationalization of banking performance, De Massis et al ( 2018) revealed that foreign assets to total global assets had a positive effect on the financial performance and value creation in meeting corporate set goals and objectives. Eshetu and Mehare (2020) established that there was a positive relationship between foreign assets and total global assets, suggesting that the extent of foreign assets accumulation in terms of current financial resources and non-current corporate growth are essentially significant in evaluating the economic justification for internationalization.…”
Section: Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Brahmana et al (2018), foreign assets to total global assets are closely associated with the internationalization of banking performance, De Massis et al ( 2018) revealed that foreign assets to total global assets had a positive effect on the financial performance and value creation in meeting corporate set goals and objectives. Eshetu and Mehare (2020) established that there was a positive relationship between foreign assets and total global assets, suggesting that the extent of foreign assets accumulation in terms of current financial resources and non-current corporate growth are essentially significant in evaluating the economic justification for internationalization.…”
Section: Internationalizationmentioning
confidence: 99%
“…On the other hand, Nigeria has witnessed some indigenous banks expanding their branches abroad. Notably, the pioneering internationalized banks were Mainstream bank ton Ireland in the year 1988, followed by other banks, First Bank in 2002 to the United Kingdom, Union Bank of Nigeria to the United Kingdom in 2004, Guarantee Trust Bank in 2007 to the United Kingdom, Zenith Bank in 2007 to the United Kingdom, United for Africa in 2008 to the United Kingdom followed by Access Bank in 2008 to the United Kingdom and First Monument Bank in 2009 to the United Kingdom respectively (Dou et al, 2019;Eshetu & Mehare, 2020). The real objectives of these banks operating outside the shores of the country have in recent times come into question.…”
Section: Introductionmentioning
confidence: 99%
“…So the involvement of nations in international trade is governed by their specialization in the production of goods in which they have a comparative advantage [1]. This theory dates back to the eighteenth century when Adam Smith realized the importance of specialization and trade in the economy [2]. More importantly, international trade would increase efficiency in resource allocation and increase world output and welfare through specialization [3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the share of developing countries in international trade has improved from 25% to 33% with a share of Africa in the international market sticking at below 3% [2]. While the share of Ethiopia remained under 0.03% [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation